1984
DOI: 10.2172/60565
|View full text |Cite
|
Sign up to set email alerts
|

Numerical studies of fluid and heat flow near high-level nuclear waste packages emplaced in partially saturated fractured tuff

Abstract: We have performed modeling studies on the simultaneous transport of heat, liquid water, vapor, and air in partially saturated fractured porous rock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1988
1988
2003
2003

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 17 publications
(7 reference statements)
0
13
0
Order By: Relevance
“…Key issues include the extent of formation dry-out and liquid-phase exclusion from regions heated above the nominal boiling point, the formation and behavior of condensation zones, the potential development of fast preferential water flow paths, the migration of transient water pulses through heated regions, and the development of heat pipe conditions. There is a long track record of mathematical modeling studies devoted to thermally driven processes in the Yucca Mountain Project [Nitao, 1989;Nitao et al, 1992;Tsang, 1993, 1994;Pruess et al, 1984Pruess et al, , 1988Pruess et al, , 1985Pruess et al, , 1990aPruess, 1987, 1989]. Additionally, there have been many theoretical and experimental studies of the behavior of heat pipes primarily in porous media [McGuinness, 1996[McGuinness, , 1997Ramesh and Torrance, 1990;Stubos et al, 1993;Udell, 1985].…”
Section: Introductionmentioning
confidence: 99%
“…Key issues include the extent of formation dry-out and liquid-phase exclusion from regions heated above the nominal boiling point, the formation and behavior of condensation zones, the potential development of fast preferential water flow paths, the migration of transient water pulses through heated regions, and the development of heat pipe conditions. There is a long track record of mathematical modeling studies devoted to thermally driven processes in the Yucca Mountain Project [Nitao, 1989;Nitao et al, 1992;Tsang, 1993, 1994;Pruess et al, 1984Pruess et al, , 1988Pruess et al, , 1985Pruess et al, , 1990aPruess, 1987, 1989]. Additionally, there have been many theoretical and experimental studies of the behavior of heat pipes primarily in porous media [McGuinness, 1996[McGuinness, , 1997Ramesh and Torrance, 1990;Stubos et al, 1993;Udell, 1985].…”
Section: Introductionmentioning
confidence: 99%
“…There is a long record of mathematical modeling studies devoted to the prediction of the future thermal-hydrological conditions in the unsaturated environment [Nitao et al, 1992;Tsang, 1993, 1994;Pruess et al, 1984Pruess et al, , 1985Pruess et al, , 1988Pruess et al, , 1990aPruess, 1987, 1989]. Typically, these studies have demonstrated that a large, superheated dry rock region will form for several thousand years at Yucca Mountain, and that during this period, infiltrating liquid water is not expected to contact waste packages.…”
Section: Motivationmentioning
confidence: 99%
“…This approximation substantially simplifies the flow problem. Pruess et al (1986) presented a model for a single equivalent continuum in unsaturated fractured rock in which hydraulic conductivity was taken as a sum of hydraulic conductivity from the porous medium and the fracture. Pruess et al (1990a,b) found that this approach was unacceptable in the presence of rapid flow transients, large fracture spacings, or with a very low permeability rock matrix.…”
Section: Single Equivalent Continuum Formulationmentioning
confidence: 99%